Noncontingent and differential reinforcement in the treatment of pediatric feeding problems. Issue 3 (10th April 2019) - Berth, Diane P.; Bachmeyer, Melanie H.; Kirkwood, Caitlin A.; Mauzy, Courtney R.; Retzlaff, Billie J.; Gibson, Amanda L.
Abstract : We conducted functional analyses of the inappropriate mealtime behavior of 5 children diagnosed with feeding problems. Then, we compared the effects of differential and noncontingent reinforcement, and the relative effects of escape extinction with and without differential or noncontingent reinforcement, when escape extinction appeared necessary. Both reinforcement procedures were effective without escape extinction to treat food refusal for 1 child, but only differential reinforcement was effective without escape extinction to treat the child's liquid refusal. Escape extinction was necessary for 4 of 5 children. The addition of positive reinforcement resulted in beneficial effects (i.e., more stable acceptance, decreased inappropriate mealtime behavior or negative vocalizations) with 3 of 4 children. With escape extinction, differential reinforcement was more effective to treat food refusal for 2 children and noncontingent reinforcement was more effective for 1 child.